Evaluation of Coronary Artery Calcium Score (CACS) in Dipper and Non-Dipper Hypertensive Patients with Moderate and High Cardiovascular Disease Risks - Ahmet Cinar; Omer Gedikli; Muhammet Uyanik; Ozlem Terzi (Medicina)
Background and Objectives: Hypertension is typically classified into two main groups, “dipper” and “non-dipper”, based on nocturnal blood pressure decline. The coronary artery calcium score (CACS) is an essential biomarker used to assess the presence and severity of coronary artery disease (CAD). This study aims to demonstrate the relationship between CACS and hypertensive patients with moderate-to-high cardiovascular disease (CVD) risk classified as either dipper or non-dipper. Participants and Methods: A total of 167 patients with moderate-to-high CVD risk were divided into two subgroups: 95 patients with dipper hypertension (HT) and 72 with non-dipper hypertension. CACS was measured using coronary computed tomography angiography. Results: In the dipper HT group, there were 60 females (63.2%) and 35 males (36.8%), whereas the non-dipper HT group included 28 females (38.9%) and 44 males (61.1%) (p = 0.002). The mean age was 57 in the dipper HT group and 62 in the non-dipper HT group (p = 0.011). The mean CACS was 93 in the non-dipper HT group and 10 in the dipper HT group (p < 0.001). A history of coronary artery disease was more common in the non-dipper HT group (p = 0.003). Smoking prevalence was higher in the non-dipper HT group (31 patients, 43.1%) compared to the dipper HT group (25 patients, 26.3%) (p = 0.023). Correlation analysis showed that CACS was positively correlated with age, BMI, and HbA1c and negatively correlated with eGFR. Higher CACS values were also observed in males and patients with a history of coronary artery disease, diabetes mellitus, and hyperlipidemia. In univariate analysis, age, male sex, smoking, CAD, CACS, and elevated creatinine were identified as significant risk factors for non-dipper HT (p < 0.05). However, in multivariate analysis, only CACS emerged as a significant independent risk factor (p = 0.001), while other variables were not significant (p > 0.05). The area under the curve (AUC) for CACS was 0.759, indicating statistically significant and excellent discriminative capability (p < 0.001, 95% CI: 0.680–0.839). Conclusions: It was concluded that non-dipper hypertension is associated with higher CACS and indicates a higher cardiovascular risk for this group.